The Affordable Care Act and the labor market: A first look - Maxim Pinkovskiy (Federal Reserve Bank of New York, 2015)
I consider changes in labor markets across U.S. states and counties around the enactment of the Affordable Care Act in 2010 and its implementation in 2014. I find that counties with large fractions of uninsured (and therefore a large exposure to the ACA) before the enactment or the implementation of the ACA experienced more rapid employment and salary growth than did counties with smaller fractions of people uninsured, both after the implementation of the ACA and after its enactment. I also find that the growth of the fraction of employees in states with larger uninsurance rates was not substantially higher than it was in states with smaller uninsurance rates. These findings are not accounted for by differential rates of recovery from the Great Recession in high- and low-uninsurance areas.
Keywords: I13; I18; 330; labor economics; health economics